Kesan Penggunaan Modul Pendekatan Muzikal Berasaskan Model Regulasi Emosi Terhadap Pengetahuan, Sikap Dan Amalan Pemakanan Murid Tahun Lima - Abdullah, Marlina (2021)
his research aims to investigate the effect of using Musical Approach Module based on the Emotion Regulation Model (PMBMRE) on the nutritional knowledge, attitude and practice of Year Five students of different genders in primary schools. In this study, PMBMRE Module was developed based on ASSURE Instructional Design Model. Pre-experimental design with pre-test, post-test and delayed post-test were used in this research. In this study, the 67 Year Five respondents were from two urban schools which consists of one boys' school (33 students) and one girls' school (34 students) in the district of Kuala Muda/Yan,Kedah, Malaysia. Nutritional Knowledge Questionnaire, Nutritional Attitude Questionnaire and Nutritional Practice Questionnaire were used to measure the knowledge, attitude and practice of Year Five students. This questionnaire is known as Nutritional Knowledge, Attitude and Practice Questionnaire (SSPSAP). The research hypotheses in this study were tested with descriptive and inferential statistic. For the inferential statistics, One Way MANOVA test, MANOVA with repeated measure, ANOVA with the repeated measure and statistical analysis of PROCESS Procedures for SPSS version 3.4.1 by Hayes (2020) were used. Collected data were analyzed using the IBM® SPSS® Statistics Version 24. Research findings showed there was an enhancement and positive retention towards students' nutritional knowledge, attitude and practice.